2017
DOI: 10.4315/0362-028x.jfp-16-417
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perceptions of the Safety of Ready-to-Eat Foods in Retail Food Store Settings

Abstract: To better understand how consumers perceive food safety risks in retail food store settings, a survey was administered to 1,041 nationally representative participants who evaluated possible food safety risks depicted in selected photographs and self-reported their perceptions, attitudes, and behaviors. Participants were shown 12 photographs taken at retail stores portraying either commonly perceived or actual food safety contributing factors, such as cross-contamination, product and equipment temperatures, wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Just as the evaluation made by our consumers between market food handlers’ training and market hygiene correlated well, other studies also detected a relationship between a stall’ s general hygiene status and the hygiene conditions of the production, handling, and distribution of the food sold by the handling staff [ 30 , 31 ], as well as its microbiological quality [ 32 ]. Ghartey and Antwi [ 33 ] also stressed that food handlers in south Ghana with a higher level of education washed their hands better.…”
Section: Discussionmentioning
confidence: 66%
“…Just as the evaluation made by our consumers between market food handlers’ training and market hygiene correlated well, other studies also detected a relationship between a stall’ s general hygiene status and the hygiene conditions of the production, handling, and distribution of the food sold by the handling staff [ 30 , 31 ], as well as its microbiological quality [ 32 ]. Ghartey and Antwi [ 33 ] also stressed that food handlers in south Ghana with a higher level of education washed their hands better.…”
Section: Discussionmentioning
confidence: 66%
“…Understanding consumers' behavior and their home practices, as well as their handling of high-risk foods is essential for reducing the number of foodborne illnesses. Several studies have reported consumers' behaviors towards RTE foods (Cates et al 2006;Evans and Redmond 2016;Van Loo et al 2010;Levine et al 2017), and evaluated how consumers perceive food safety risks in retail food store settings, using selected photographs and self-reported perceptions, attitudes, and behaviors, where consumers with a food science background had more knowledge about factors contributing to food safety risks than the average focus group participant. Jevšnik et al (2008) reported that Slovenian consumers were not familiar with their role in the food safety chain or with the importance of maintaining a cold chain, and consequently allowing numerous opportunities for microbiological contamination of food (Jevšnik et al 2008).…”
Section: Introductionmentioning
confidence: 99%